Polymer-Drug Conjugates: Novel Carriers for Cancer Chemotherapy. Issue 2 (22nd January 2019) - Seifu, Muluneh Fromsa; Nath, Lila Kanta
ABSTRACT: Cancer is the second worldwide cause of death following cardiovascular diseases. Chemotherapy is the gold standard strategy for effective treatment of cancer. However, the use of free chemotherapeutic agents in cancer treatment has been hindered by poor aqueous solubility, short biological half-life, non-speciﬁcity or dose-dependent cellular toxicity, and the development of multidrug resistance. To address the aforementioned limitations, polymer-drug conjugations, among other novel drug delivery approaches, are receiving attention in cancer therapy. In this review the concept of polymer–drug conjugations, polymer–drug conjugates as drug carriers, polymer-drug coupling methods, and recent polymer-anticancer drugs conjugates have been described.